Discriminating between Waldenström macroglobulinemia and marginal zone lymphoma using logistic LASSO regression. Issue 5 (16th April 2022) - Amaador, Karima; Vos, Josephine M. I.; Pals, Steven T.; Kraan, Willem; Dobber, Johan A.; Minnema, Monique C.; Koene, Harry R.; de Bruin, Peter C.; Zwinderman, Aiko H.; Kersten, Marie José
Abstract: Discrimination between Waldenström macroglobulinemia (WM) and marginal zone lymphoma (MZL) of the bone marrow (BM) can be difficult due to overlap in clinical, histopathologic, and immunophenotypic characteristics. We determined which characteristics can aid in the differential diagnosis of 'gray zone' cases. We compared clinical, histopathologic, immunophenotypic, and molecular features of 222 WM and 65 MZL patients. LASSO regression was employed for variable selection. The most distinguishing clinical features of WM compared to MZL were the presence of the B-symptom weight loss and IgM paraprotein. Histopathological findings were plasmacytoid differentiation, monoclonal plasma cells, and increased mast cells in the BM. Regarding flow cytometry, only CD10 and CD38 were distinguishing markers. Finally, as the expected presence of the MYD88 L265P mutation showed to be of great value in the distinction between WM and MZL. Despite the great overlap, WM can often be distinguished from MZL by using a combination of characteristics. These characteristics should be weighed in complex, 'gray zone' cases.